1997
DOI: 10.1021/ie960223r
|View full text |Cite
|
Sign up to set email alerts
|

Nonterminating Polymerizations in Continuous Flow Systems

Abstract: The feasibility of manufacturing narrow polydispersity polymers in continuous flow systems is explored. The method of moments is applied to ideal and more realistic kinetic schemes in a variety of reactor types. In most cases, polydispersities approaching those obtained in batch can also be achieved in continuous reactors, but the long-term stability of a tubular reactor with species-dependent, radial diffusion remains in doubt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…In ideal plug flow reactors under steady-state conditions, polymers with the same characteristics of the MWD as in batch reactors are built -the time axis is transformed to the length axis of the plug flow reactor [74,75], and for fast initiation the MWD is a Poisson distribution. For laminar plug flow reactors [75,76] some broadening of the distribution is observed, depending on ½M 0 =½I 0 and conversion. The long-term stability of laminar flow tubular reactors is questioned [76], because of the possibility of very long chains growing near the reactor walls, where the residence time approaches infinity, if radial diffusion of the monomer occurs from the inner tube to the walls.…”
Section: Molecular Weight Distribution Of Living Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…In ideal plug flow reactors under steady-state conditions, polymers with the same characteristics of the MWD as in batch reactors are built -the time axis is transformed to the length axis of the plug flow reactor [74,75], and for fast initiation the MWD is a Poisson distribution. For laminar plug flow reactors [75,76] some broadening of the distribution is observed, depending on ½M 0 =½I 0 and conversion. The long-term stability of laminar flow tubular reactors is questioned [76], because of the possibility of very long chains growing near the reactor walls, where the residence time approaches infinity, if radial diffusion of the monomer occurs from the inner tube to the walls.…”
Section: Molecular Weight Distribution Of Living Polymersmentioning
confidence: 99%
“…For laminar plug flow reactors [75,76] some broadening of the distribution is observed, depending on ½M 0 =½I 0 and conversion. The long-term stability of laminar flow tubular reactors is questioned [76], because of the possibility of very long chains growing near the reactor walls, where the residence time approaches infinity, if radial diffusion of the monomer occurs from the inner tube to the walls.…”
Section: Molecular Weight Distribution Of Living Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al [10] continuously synthesized homopolymers or block copolymers with controlled MWs using an ATRP in a packedcolumn reactor. These previous experimental and theoretical studies indicated that continuous CLRP techniques can be used in polymer engineering [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial literature exists concerning the modeling of such reactors in different contexts. A good overview is given by Dotson et al [1] Simulations in continuous reactors have been carried out for long chain branching, [2] copolymerization, [3,4] emulsion polymerization, [4] living polymerization, [5] multi-component chain growth reactions, [6] and for various other aspects of specific polymers such as nylon 6, [7] poly-(methyl methacrylate), [8] poly(vinyl acetate) (modeling and experiments), [9] and polystyrene. [10] Scale up modeling to full scale industrial reactors has also been made.…”
Section: Introductionmentioning
confidence: 99%